Long-term outcome of a mental health promotion program in Germany - Lyssenko, Lisa; Kleindienst, Nikolaus; Schmahl, Christian (Health promotion international, 2019)
Summary. Mental health promotion programs (MHP) seek to reduce sub-syndromal symptoms of mental distress and enhance positive mental health. This study evaluat